2013
DOI: 10.1093/infdis/jit508
|View full text |Cite
|
Sign up to set email alerts
|

Noncalcified Coronary Atherosclerotic Plaque and Immune Activation in HIV-Infected Women

Abstract: NCT00455793.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
202
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(226 citation statements)
references
References 25 publications
17
202
5
2
Order By: Relevance
“…May use atorvastatin or rosuvastatin with caution (start with the lower possible dose and titrate based on tolerance and lipid-lowering efficacy). Avoid atorvastatin with TPV found in relatively young HIV-infected patients [14,15]. HIV suppression remains the standard in CVD reduction, as studies have suggested that higher CD4 cell counts and lower HIV RNA levels are associated with a decrease in MI risk [37,64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…May use atorvastatin or rosuvastatin with caution (start with the lower possible dose and titrate based on tolerance and lipid-lowering efficacy). Avoid atorvastatin with TPV found in relatively young HIV-infected patients [14,15]. HIV suppression remains the standard in CVD reduction, as studies have suggested that higher CD4 cell counts and lower HIV RNA levels are associated with a decrease in MI risk [37,64].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are not only limited to the male HIV-infected population. A study that focused on the female HIV population found that young, asymptomatic HIV-infected women also demonstrate increased NCAP [15]. This has led to a surge in interest in the association between HIV infection and CVD, specifically NCAP due to the increase of major adverse cardiac events (MACE) associated with it [16].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of coronary plaques was similar in both groups, but HIV-infected females had a significantly higher prevalence of non-calcified coronary artery plaques (35% vs 12% in female control subjects; p=0.04) which remained significant even after adjustment for CV risk factors such as age, race, FRS, smoking status, levels of triglycerides (TGs), HDL-c and LDL-c, and BMI. The percentage of coronary segments with non-calcified plaques was significantly higher in HIV-infected women (median 75% IQR 63%-100%) compared to HIV-infected men (median 50% IQR 3%-100%; p<0.05,) [26] which is important because non-calcified plaques are considered vulnerable and more susceptible to rupture leading to acute coronary syndromes [27]. Coronary artery calcium scores (CAC) have been found to be higher in HIV-infected patients with metabolic syndrome compared to those without metabolic syndrome [20].…”
Section: Computed Tomography Coronary Angiography (Cta)mentioning
confidence: 86%
“…The same study showed that HIV-infected women had higher rates of metabolic syndrome compared with HIV-infected men. Conversely, another study found that HIV-uninfected women had statistically significant higher percentage of CAC >100 (p=0.02) compared to HIV-infected women [26]. Other studies did not demonstrate gender differences in CAC [20,28].…”
Section: Computed Tomography Coronary Angiography (Cta)mentioning
confidence: 90%
See 1 more Smart Citation